Analysis and Implementation of 3-D Transpositional Cipher Algorithm Based on Rubik’s Cube Mechanism - Vilasini, V.; Vasudevan, V.; Nanthan, S. Manuj; Roy, K. Lakshmi Kalpana (Journal of Soft Computing Paradigm, 2023)
The algorithms that are used for encrypting the text information for security purpose are referred as encryption algorithms. They are widely employed for the application on data transmission over networks. This is seen as a necessary part of data transmission since confidentiality and data privacy are important factors. Different encryption algorithms have different complexities, speeds of execution, and degrees of security. The Advanced Encryption Standard (AES) is one of the algorithms acknowledged by the U.S. government and other major organizations. The AES algorithm guarantees high security since there is no known public attack that can crack it. The Blowfish algorithm on the other hand is very fast but less secure. The encryption algorithms in the average zone of these two algorithms are highly useful for the transmission of general information among people. Such an algorithm also guarantees a good amount of speed as well as more security. Non-conventional algorithms such as transpositional cipher based on Rubik’s Cube mechanism can be seen as a viable option to use in common applications. These algorithms can be further deepened with the help of more complex key generation parts that can be done to enhance the security of the data. This paper focuses on analytically evaluating if this algorithm can be treated as a viable replacement in an application compared to other algorithms. Moreover, this research covers some pros and cons noted while evaluating.
Keywords: AES; DES; Rubik Cube Algorithm; FCM